Implementation of Online Learning at SD Muhammadiyah 4 Zam Zam Sukodono - Octavia Nur Fadilah (Proceedings of The ICECRS, 2021)
After more than one year of the Covid19 pandemic there have been many sectors affected by the Covid19 pandemic, education is one of the sectors that has felt the impact of the COVID-19 pandemic. The purpose of this research is to find out how an institution in education implements or applies online learning in the midst of the COVID-19 pandemic. This research is a research through observation to a place / instance or object that has been determined, by digging data through sources who are willing to provide information related to the articles made. In this research regarding the application of online learning, there are several difficulties or obstacles that occur when online learning is implemented. So as to make the school change the application system by looking for a learning system that is more effective to apply.